The role of electronic media in combating mercenary recruitment By ISIS terrorist gangs - Alaa Moussa Badr Al-Alawi, Asst. Lect. (lark, 2025)
The responsibility of the media person is evident through his use of the media for the purpose of publishing advertisements that are consistent with the values ​​of society and the rules of the law. The media institution that wants to advertise the product must ensure the accuracy of the information related to the advertisement, so that the advertisement is not misleading and exposes it to liability. Electronic media has an important role in recruiting a mercenary, who is considered a person who actively participates in armed conflicts in exchange for obtaining money. It has no principles to defend, nor is it governed by values ​​or laws in the field of conflicts. One of the reasons for the research is that in order for the media to achieve its role, there must be a means through which it can deliver its message to the largest possible audience. The research aims to answer the main question: What is the position of electronic media in Iraq on recruiting mercenaries? To prove the original hypothesis, which is that electronic recruitment has difficulty proving the perpetrators, and the lack of information and evidence that proves that the person recruited is considered a perpetrator, and that electronic recruitment tools are characterized by the fact that they are used via the Internet in its various forms, whether on a computer, mobile phone, or any other technological form, and we reached a number of results, including that electronic recruitment tools are subject to actual monitoring by the state, and identifying the actual user of the website, Monitoring programs and Internet networks, with the aim of reaching the recruited person and revealing the identity of the person who sends messages and instructions to follow him via the Internet, and conducting supervision and control of electronic information systems used in electronic media.